Survei Motivasi Belajar Siswa Mata Pelajaran Pendidikan Jasmani Olahraga dan Kesehatan Via Sistem Pembelajaran Daring Kelas X SMK Muhammadiyah 1 Sukabumi Tahun Pelajaran 2019/2020 - Firman Maulana; Gartika Sabri Ningtyas; Wening Nugraheni (Universitas PGRI Semarang, 2021)
This research is to find out students’ motivation in physical education and sport physical education through online learning in class X Muhammadiyah 1 Vocational High School Sukabumi 2019/2020 Academic Year. This study uses a descriptive survey method with a questionnaire for data collection techniques. The subjects in this study were five majors of class X in Muhammadiyah 1 Vocational High School Sukabumi in the 2019/2020 Academic Year with a total of 112 students so they were conducted in class X SMK Negeri 3 Sukabumi with a validity coefficient of 0.890 and reliability of 0.891. This research analysis technique uses quantitative descriptive through the form of a percentage. The results of this study indicate that students’ motivation in physical education sports and health via the online learning system class X in Muhammadiyah 1 Vocational High School Sukabumi 2019/2020 Academic Year is in the “high” category with a percentage of 11.61% 13 students, “moderate” 76.78% 86 students, and “low” 11.61% 13 students. It can be concluded that the students’ motivation in physical and sports physical education subjects via the online learning system class X in Muhammadiyah 1 Vocational High School Sukabumi 2019/2020 Academic Year is in the category of “medium”.Keywords: Learning Motivation, PJOK, Online Learning System, Class X Students. AbstrakPenelitian ini untuk mengetahui motivasi belajar siswa mata pelajaran pendidikan jasmani olahraga dan kesehatan melalui pembelajaran daring kelas X SMK Muhammadiyah 1 Sukabumi Tahun Pelajaran 2019/2020. Penelitian ini menggunakan penelitian deskriptif metode survei dengan instrumen angket kuesioner untuk teknik mengambilan data. Subjek dalam penelitian ini adalah lima jurusan kelas X di SMK Muhammadiyah 1 Sukabumi Tahun Pelajaran 2019/2020 dengan jumlah 112 siswa sehingga disebut penelitian populasi, dan uji coba dilaksanakan di kelas X SMK Negeri 3 Sukabumi dengan koefisien validitas sebesar 0.890 dan reliabilitas sebesar 0.891. Hasil dari penelitian ini menunjukkan bahwa motivasi belajar siswa mata pelajaran pendidikan jasmani olahraga dan kesehatan via sistem pembelajaran daring kelas X SMK Muhammadiyah 1 Sukabumi Tahun Pelajaran 2019/2020 ada pada kategori “tinggi” dengan jumlah presentase 11.61% 13 siswa, “sedang” 76.78% 86 siswa, dan “rendah” 11.61% 13 siswa. Dapat disimpulkan bahwa motivasi belajar siswa mata pelajaran pendidikan jasmani olahraga dan kesehatan via sistem pembelajaran daring kelas X SMK Muhammadiyah 1 Sukabumi Tahun Pelajaran 2019/2020 berada pada kategori “sedang”.Kata kunci: motivasi belajar;PJOK, sistem pembelajaran daring, siswa kelas X